SLACK RESOURCES AND CORPORATE SUSTAINABILITY PERFORMANCE - Ibrahim, Rofi Dwi Bagus; Larasati, Ika Putri (Universitas Jember, 2024)
ABSTRACTCorporate Sustainability Performance (CSP) is an important issue and has received considerable attention from stakeholders. CSP practices require the availability of resources from the company. Slack resources are surplus resources in a company that can be utilized for CSP. Slack resources in this research are classified into financial slack and Human Resources (HR) slack. This research aims to examine the role of financial slack and HR slack on CSP. The number of samples in this research was 250 non-financial companies that publish sustainability reports and annual reports and are listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. This quantitative research uses multiple linear regression analysis with the Newey-West standard error approach. The research results show that financial slack does not affect CSP, while HR slack has a positive effect on CSP. This finding is because the allocation of financial slack tends to be more rigid when compared with the allocation of HR slack for CSP.Keywords: Corporate Sustainability Performance; Financial Slack; Human Resources Slack; Slack Resources ABSTRAKCorporate Sustainability Performance (CSP) merupakan isu penting dan mendapat banyak perhatian bagi para pemangku kepentingan. Praktik CSP pada dasarnya memerlukan ketersediaan sumber daya dari perusahaan. Slack resources adalah sumber daya yang berlebih di suatu perusahaan sehingga dapat dimanfaatkan untuk CSP. Slack resources dalam penelitian ini diklasifikasikan menjadi kelebihan sumber daya keuangan (financial slack) dan kelebihan sumber daya manusia (human resources slack). Penelitian ini bertujuan untuk menguji peran financial slack dan Human Resources (HR) slack terhadap CSP. Jumlah sampel dalam penelitian ini sebanyak 250 perusahaan non-keuangan yang mempublikasikan sustainability report dan annual report, serta terdaftar di Bursa Efek Indonesia (BEI) periode 2018-2022. Penelitian kuantitatif ini menggunakan analisis regresi linear berganda dengan pendekatan Newey-West standard error. Hasil penelitian menunjukkan bahwa financial slack tidak berpengaruh terhadap CSP, sementara HR slack berpengaruh positif terhadap CSP. Temuan ini dikarenakan alokasi financial slack cenderung lebih rigid, jika dibandingkan dengan alokasi HR slack untuk CSP.Kata Kunci: Corporate Sustainability Performance; Financial Slack; Human Resources Slack; Slack Resources